DUE TO LEGAL CANCELLATION OF LAND PURCHASE DEED - Indrati Rini (International Journal of Social Science, 2023)
Deed of sale and purchase of land as evidence of the transfer of ownership rights to land, including the buildings/houses on it. The transfer of ownership rights to land can be done through a sale and purchase agreement. The land sale and purchase agreement, including the building/house on it, must be carried out by the parties before an authorized official, namely a Notary/Land Deed Making Officer. To ensure legal certainty of the transfer of ownership rights to land, it is stated in the form of an authentic deed. The validity of the land sale and purchase deed is determined by the legal terms of the agreement which must be fulfilled by the seller and the buyer. The deed of sale and purchase of land can be canceled by a judge, which in practice, cases often occur which give rise to legal consequences for the cancellation of the deed of sale and purchase of land.